The Influence of Work Attitudes on Student Achievement at SMK Negeri 1 Tomohon - Kaligis, Gerry; Dakhi, Aspirasi (JURNAL EDUNITRO Jurnal Pendidikan Teknik Elektro, 2023)
This research is motivated by the influence of work attitudes on student achievement. Students can now act quickly due to several factors of the times and technology that affect student attitudes in the learning process, affecting their learning achievement. The purpose of this study was to determine work attitudes towards student achievement. This research uses an experimental method with a quantitative approach to determine the effect between variables. The data collection technique used was a questionnaire for work attitudes, while student achievement was obtained from the student score document. The data analysis technique used is a simple linear regression test. The results of this study indicate that there is an effect of work attitude on student achievement. Based on the results of this study, it can be said that if the work attitude impacts the high student learning achievement and vice versa, if the work attitude is low, it will also impact the low student achievement.